Identification and Evaluation of Novel MicroRNA Biomarkers in Plasma and Feces Associated with Drug-induced Intestinal Toxicity. (February 2017) - Kalabat, Dalia Y.; Vitsky, Allison; Scott, Wesley; Kindt, Erick; Hayes, Kyle; John-Baptiste, Annette; Huang, Wenhu; Yang, Amy H.
Gastrointestinal toxicity is dose limiting with many therapeutic and anticancer agents. Real-time, noninvasive detection of markers of toxicity in biofluids is advantageous. Ongoing research has revealed microRNAs as potential diagnostic and predictive biomarkers for the detection of select organ toxicities. To study the potential utility of microRNA biomarkers of intestinal injury in a preclinical toxicology species, we evaluated 3 rodent models of drug-induced intestinal toxicity, each with a distinct mechanism of toxicity. MiR-215 and miR-194 were identified as putative intestinal toxicity biomarkers. Both were evaluated in plasma and feces and compared to plasma citrulline, an established intestinal injury biomarker. Following intestinal toxicant dosing, microRNA changes in feces and plasma were detected noninvasively and correlated with histologic evidence of intestinal injury. Fecal miR-215 and miR-194 levels increased, and plasma miR-215 decreased in a dose- and time-dependent manner. Dose-dependent decreases in plasma miR-215 levels also preceded and correlated positively with plasma citrulline modulation, suggesting miR-215 is a more sensitive biomarker. Moreover, during the drug-free recovery phase, plasma miR-215 returned to predose levels, supporting a corresponding recovery of histologic lesions. Despite limitations, this study provides preliminary evidence that select microRNAs have the potential to act as noninvasive, sensitive, and quantitative biomarkers of intestinal injury.